Absolute Power, Absolute Venality: The Politics of Corruption and Anti-corruption in Malaysia. (2nd January 2022) - Siddiquee, Noore Alam; Zafarullah, Habib
Abstract : Although corruption in Malaysia is nothing new, it has exacerbated in recent years as reflected in the deteriorating corruption perceptions index and a series of large-scale corruption scandals that have made headlines around the world. Lately, corruption has become so endemic and widespread that Malaysia has earned the dubious distinction of a kleptocracy, notwithstanding ongoing anti-corruption campaigns. This paper examines and analyses Malaysia's anti-corruption experience and the factors that explain it. Drawing on data from both primary and secondary sources it argues that anti-corruption drives have remained narrowly-focused, ignoring some critical aspects of Malaysia's political economy including the politics-business nexus, patronage networks and money politics which are at the heart of grand corruption. It further argues that much of the high-level corruption has its roots in politics and that the powerful political figures have remained largely untouched by anti-corruption drives. Finally, it reveals that despite institutional revamp, key institutions continue to suffer from a lack of independence and effective power. Such constraints, reinforced further by political manipulation and selective application of laws, have undermined the effectiveness of anti-corruption initiatives. The Malaysian experience offers lessons and insights that have wider relevance.